2010
DOI: 10.2522/ptj.20090168
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Exercise Alters Analgesia and Neurotrophin-3 Synthesis in an Animal Model of Chronic Widespread Pain

Abstract: This is the first study demonstrating the effect of exercise on deep tissue mechanical hyperalgesia in a rodent model of pain and providing a possible molecular basis for exercise training in reducing muscular pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
2
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 55 publications
2
54
2
5
Order By: Relevance
“…The obtained results from this study showed that increased activity in the form of moderate endurance exercise can improve neuropathic pain responses in mechanical allodynia and thermal hyperalgesia. This result is consistent with some studies suggesting the significant effects of exercise training on neuropathic pain responses in various pain models (11,15). Conversely, some studies have failed to confirm the effects of exercise training on improvement of neuropathic pain (17).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The obtained results from this study showed that increased activity in the form of moderate endurance exercise can improve neuropathic pain responses in mechanical allodynia and thermal hyperalgesia. This result is consistent with some studies suggesting the significant effects of exercise training on neuropathic pain responses in various pain models (11,15). Conversely, some studies have failed to confirm the effects of exercise training on improvement of neuropathic pain (17).…”
Section: Discussionsupporting
confidence: 81%
“…At first, during the orientation phase and in order to habituate to laboratory conditions (treadmill and manipulation exercises), the animals were given exercise on a treadmill, 5 days a week for 10 -15 minutes at a speed of 10 m/min. The rats were exposed to behavioral testing for 3 days (2 times for each testing) for adaptation to behavioral tests (15). 2 weeks after induction of diabetes and by re -running pain behavioral tests, as well as ensuring incidence of neuropathic pain in diabetic groups, the endurance exercise protocol was then carried out for 6 weeks (14).…”
Section: Methodsmentioning
confidence: 99%
“…Most of these studies started exercise at the time of injury or after development of hyperalgesia and show a reversal of the hyperalgesia with as little as a single treatment (3,33,51,58). However, Kuphal and colleagues show that 7 days of exercise prior to induction of inflammatory pain with formalin or 2 wk of exercise prior to induction of neuropathic pain attenuated the development of pain behaviors.…”
Section: Exercise Effects In Animal Models Of Painmentioning
confidence: 99%
“…This concept is at the foundation of the biopsychosocial model of pain. 11 Experimental evidence suggests that pain due to early-stage (regional) central sensitization 38,62 versus late-stage (widespread) central sensitization 57 may be modulated in distinct ways. QST may help stage nociceptive processing and thereby improve efficacy in patient care.…”
Section: Clinical Application Of Quantitative Sensory Testing In Muscmentioning
confidence: 99%
“…38,57,62 QST may be an ideal clinical outcome measure for identifying somatosensory patterns typically associated with certain stages of altered nociception and for documenting pain modulation. 39 Finally, identification of nociceptive mechanisms and quantitative sensory changes in patients with chronic musculoskeletal dysfunction may help explain some previously controversial clinical examination findings.…”
Section: Quantitative Sensory Testingmentioning
confidence: 99%